Data for "Hot-carrier transfer across a nanoparticle-molecule junction: The importance of orbital hybridization and level alignment" - Fojt, Jakub; Rossi, Tuomas; Kuisma, Mikael; Erhart, Paul (Chalmers University of Technology, 2022)
This upload includes the data presented and analyzed in the article "Hot-carrier transfer across a nanoparticle-molecule junction: The importance of orbital hybridization and level alignment" by Jakub Fojt, Tuomas P. Rossi, Mikael Kuisma, and Paul Erhart.

The codes for reproducing the data are provided at doi:10.5281/zenodo.7118376.

See README.md in data.zip for a detailed description.
Keywords: Physical Sciences; Fysik